Performance of Native Fluorescent Pseudomonas on in vitro Seed Germination and Seedling Vigour of Sorghum bicolor (L.) Moench - Basha, S. Ameer; Raghavendra, G.; Kumar, M. V. Nagesh; Reddy, K. Dharma; Sudhakar, R. (International Journal of Bio-resource and Stress Management, 2023)
Plant Growth Promoting Rhizobacteria (PGPR) used in the production of biofertilizers is an effective and economic means to control plant diseases. They enhance seed emergence, plant growth, and yield. Rhizospheric soils of different crops like sunflower, chilli, cotton, groundnut, chickpea, sorghum etc., cultivated in Telangana region of Andhra Pradesh, India, were collected and processed for the isolation of Pseudomonas fluorescens (Pf) strains. A total of fifty four strains were identified as Pf, and growth promotion test was conducted, thirty three isolates showed potent growth promotion activity and the study exhibited a good picture of efficiency and interaction of Pf strains isolated. Maximum Vigour Index-I was shown by Pf2 whereas Pf8 strain recorded minimum.